The contribution of connected vehicles to network traffic control: A hierarchical approach. (June 2022) - Moradi, Hossein; Sasaninejad, Sara; Wittevrongel, Sabine; Walraevens, Joris
Abstract: Connected vehicles (CVs) can considerably contribute to traffic control in the near future by providing real-time information. Such information can be exploited to identify the current traffic condition. However, challenges resulting from a high volume of data and lack of perfect knowledge in mixed traffic scenarios (consisting of CVs and conventional vehicles) have led to relatively sparse research in network-wide CV-based traffic control. To deal with such challenges, this paper proposes a hierarchical framework integrating three layers: (i) an intersection controller at individual intersections located in the center of the network, (ii) a network controller to regulate traffic coming into the network, and (iii) a phase controller to optimize the sequence of intersections' signals. This approach permits the inclusion of information of (a limited number of) CVs to estimate and control queue lengths at individual intersections as well as the overall network load. Simulations carried out in VISSIM validate our approach in comparison with alternative control systems such as the application of (1) a traffic-responsive control, (2) a traffic accumulation regulator, or (3) a network signals coordinator. Moreover, comparisons between the proposed framework and a central system equipped with the information of all vehicles (giving rise to the optimal operation with, however, costly computation) under the consideration of different penetration rates of CVs and network layouts confirm that this framework results in competitive performance indicators, which, owing to the hierarchical structure, can be efficiently employed in real-time applications.